The Effects of Judical Bodies’ Interpretation Forms Of Legal Rules in Turkey on the Education Freedom in Universities - Güloğlu, Yavuz (Mevlut AYDOGMUS, 2018)
The freedom of conscience and belief can be defined as the freedom of people in what they wish to believe without the compulsion of political power and other people by means of laws and other means. The belief of religion that can be accepted as the natural extension of the freedom of conscience and belief is to be free in doing the requirements of the religion that the people believe in with its rituals. While it is not possible and effective to make restrictions in freedom of belief, today, there are some restrictions in some judical systems in freedom of worship. With the principle of secularism which is settled among the principles that the alteration of which are not even be proposed, there have been some different decisions about the administrative acts that cause the violation of belief and worship freedom in the implementation of the right of education which is secured with Constitutional Law in Turkish Constitution. In this study, the effects of the incompatible decisions of administrative jurisdiction about the implementations of the administration related to the education right of students at universities, which is secured by the Fundemental Law, on the freedom of education, especially for the last ten years, will be examined.
Keywords: Freedom of belief; freedom of worship; secularism; 4. Education; 16. Peace & justice